Community Economic Distress and Changes in Medicare Patients' End-of-Life Care Costs. - Weeks, Bill; Ouayogodé, Mariétou H.L.; Ventelou, Bruno; Mackenzie, Todd; Weinstein, James (Journal of Palliative Medicine, 2018)
Abstract